Use of clay from a local source for calcination and subsequent preparation of the mixed cement. Issue 1 (November 2021) - Smirova, B; Sedlacik, M; Novotny, R
Abstract: This paper deals with the use of calcinated clay and micronized limestone as supplementary cementitious materials (SMCs) for preparation of blended Portland cement CEM II/B-M (Q-LL). Clay used in this study was calcinated at 700°C and pozzolanic activity after calcination was assessed using accelerated R3 pozzolanic test and modified Chapelle test. The influence of calcinated clay and limestone addition on mechanical properties and hydration process was investigated and an optimal ratio for 35% clinker replacement was found. Initial decrease of mechanical strength at early ages, caused by SCM addition, was almost compensated during maturation of the binder.